A review of technological advances and open challenges for oil and gas drilling systems engineering. Issue 4 (26th November 2019) - Epelle, Emmanuel I.; Gerogiorgis, Dimitrios I.
Abstract: The ever‐increasing quest to identify, secure, access, and operate oil and gas fields is continuously expanding to the far corners of the planet, facing extreme conditions toward exploring, securing, and deriving maximum fluid benefits from established and unconventional fossil fuel sources alike: to this end, the unprecedented geological, climatic, technical, and operational challenges have necessitated the development of revolutionary drilling and production methods. This review paper focuses on a technological field of great importance and formidable technical complexity—that of well drilling for fossil fuel production. A vastly expanding body of literature addresses design and operation problems with remarkable success: what is even more interesting is that many recent contributions rely on multidisciplinary approaches and reusable Process Systems Engineering (PSE) methodologies—a drastic departure from ad hoc/one‐use tools and methods of the past. The specific goals of this review are to first review the state‐of‐art in active fields within drilling engineering and explore currently pressing technical problems, which are in dire need or have recently found, PSE‐ and/or computational fluid dynamics‐relevant solutions. Then, we illustrate the methodological versatility of novel PSE‐based approaches for optimization and control, with an emphasis on contemporary problems. Finally, we highlight current challenges and opportunities for truly innovative research contributions, which require the combination of best‐in‐class methodological and software elements in order to deliver applicable solutions of industrial importance.